Graffiti and Urban Space: the “Child of Painting” - Cambil Hernández, María de la Encarnación (Quiroga. Revista de patrimonio iberoamericano, 2012)
Graffiti has become a multicultural artistic expression, which presence in the cities modifies the reading of urban space. In this article, we analyze these “pictorial demonstrations” from the point of view of art history as an art form that has an immense creative diversity and, from a multicultural perspective, as a form of expression that it is present throughout the world. We take as a reference the analysis of this graphic expression in the city of Granada, through the work of a graffiti writer whose tang is Sex, but is better known by the alias of “The Child of the Paintings”.